ENHANCING OVERBURDEN PRODUCTION ACHIEVEMENT THROUGH LEAN SIX SIGMA: A CASE ANALYSIS OF PIT WEST MHY MINING OPERATIONS AT PT ABC BY PT XYZ - Kevin Satrio Adiguna; Nur Budi Mulyono (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This research examines the persistent problem of underachievement in overburden (OB) production at Pit West MHY, part of PT ABC’s mining operations, where actual production averaged only 63% of the planned target of Q1 2025. Overburden removal at this site is managed by PT XYZ as the mining contractor. Applying the Lean Six Sigma DMAIC framework, this research systematically identified and analyzed operational inefficiencies contributing to production shortfalls, including long hauling roads slippery after rain, lack of road maintainance (RM) equipment, hauling road damage, truck’s long cycle time, delays during shift changes, limited number of dozing unit at disposal, and queuing at loading fronts. Data sources included internal production reports, time studies, loss time records, and structured discussions with the supervisory team of PT ABC and operational staff of PT XYZ to confirm root causes. Various Lean Six Sigma tools, such as Pareto analysis, time studies, hypothesis testing, cause-and-effect diagrams, and field observations, were used to identify, analyze, and validate these root causes. Targeted improvement actions were implemented, such as addition of RM unit, hot seat change shift procedures, partial resurfacing of critical hauling road segments, additional dozer allocation to improve disposal readiness, and truck fleet split strategies to reduce congestion at loading points. As a result, average daily production achievement increased significantly to over 102% of the target on April 2025. To maintain these gains, standardized daily inspections using Condition Index forms for Haul Road, Front Loading, and Disposal areas were adopted as part of routine operational controls. This research shows that applying the Lean Six Sigma approach can deliver practical and measurable improvements to production reliability in mining operations.